Bolivia : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Bolivia. (IMF Staff Country Reports; Country Report ;, 2021)
Following the October 2020 election, the new administration moved to tackle the devastating human and economic effects of the COVID-19 pandemic. The economy shows signs of recovery from its 8.8 percent contraction in 2020. However, fiscal imbalances have increased and international reserves continue to fall. On February 12, Bolivia repurchased the 240.1 million SDR purchase under the Fund's Rapid Financing Instrument (that was approved by the Fund's Executive Board in April 2020).